The effects of acute care hospitalization on health and cost trajectories for nursing home residents: A matched cohort study. Issue 41 (14th October 2022) - Kajdacsy-Balla Amaral, Andre Carlos; Hill, Andrea D.; Pinto, Ruxandra; Fu, Longdi; Morinville, Anne; Heckman, George; Hébert, Paul; Hirdes, John
Abstract : Thirty five percent to sixty seven percent of admissions to acute care hospitals from nursing homes are potentially preventable. Limited data exist regarding clinical and cost trajectories post an acute care hospitalization. To describe clinical impact and post-hospitalization costs associated with acute care admissions for nursing home residents. Analysis of population-based data. The 65, 996 nursing home residents from a total of 645 nursing homes. Clinical outcomes assessed with the Changes in Health, End-stage disease and Symptoms and Signs (CHESS) scores, and monthly costs. Post-index date, hospitalized residents worsened their clinical conditions, with increases in CHESS scores (CHESS 3 + 24.5% vs 7.6%, SD 0.46), more limitations in activities of daily living (ADL) (86.1% vs 76.0%, SD 0.23), more prescriptions (+1.64 95% CI 1.43‐1.86, P < .001), falls (30.9% vs 18.1%, SD 0.16), pressure ulcers (16.4% vs 8.6%, SD 0.37), and bowel incontinence (47.3% vs 39.3%, SD 0.35). Acute care hospitalizations for nursing home residents had a significant impact on their clinical and cost trajectories upon return to the nursing home. Investments in preventive strategies at the nursing home level, and to mitigate functional decline of hospitalized frail elderly residents may lead to improved quality of care and reduced costs for this population. Pre-hospitalization costs were not different between the hospitalized and control groups but showed an immediate increase post-hospitalization (CAD 1882.60 per month, P < .001).